Techno-Politic and Depoliticzation in the Philosophy of Slavoj Žižek - Sherzad Ahmad Najjar; Idrees Omar Mustafa (QALAAI ZANIST JOURNAL, 2023)
The concept of politics as the fields of power, conflict and popular participation has been considered one of the most important aspects of political philosophy since the Greek era. This conceptualization has always played a major role in the "differences" and "contradiction" of its constituent elements, including ideology as an analytical framework, vision and action. Slavo Žižek tries to deconstruct the concept of politics by criticizing the basic principles of liberal democracy. He adopts a Hegelian-Marxist perspective and benefits Jacques Lacan’s psychoanalysis. He looks at politics as a field of compromise and consensus that expresses itself in bio-politics or living dominant power over life and controls all aspects of human life. In his political philosophy, Žižek reconstructs this in the context of class struggle. By highlighting the ideological dimensions behind multicultural discourse and identity politics, Žižek explains the ideological aspects and the reality of bio-politics and technocrats in which democracy is marginalised and people play a more legitimizing role, creating the problem of depoliticization. The outline of this research is as follows. The first part defines and focuses on the concepts of bio-authority, global capitalism, micro-politic and disaster capitalism. In the second part, the article focuses on authority of Control and discipline, technocrasy an democracy, relation between post-politics and political action. In the last part the articl analysis the violence and depoliticzatoin, transforming the will of people into the authority of technocrats, violence and fear of politics as a paradgaim of real politics, according to Žižek, these all lead to the closure of the political field.